Penurunan Kualitas Savana Bekol sebagai Feeding Ground bagi Rusa (Cervus timorensis) dan Banteng (Bos javanicus) di Taman Nasional Baluran Jawa Timur - Djufri Djufri (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2009)
This research aim to  know : (1). species of grass eaten by deer and species of grass predominating area of savannah Bekol. (2). Species eaten by bull, and (3). Factors causing downhill it  quality of savannah Bekol. Method used for inventories of species eaten by deer and bull is  method of transek combined with method  square. While to collect data of  factors causing downhill it  quality of savannah of Bekol with  direct perception  in  field and muster relevant information  from data sekunder. The conclusion  from  this research is (1). Found  12 species of grass eaten by deer, and 3 species among others as dominant species that is bayapan (Brachiaria reptans), red lamuran (Dichantium coricosum), and  tuton (Dactyloctenium aegyptium). (2). found  50  species as food of bull in savannah Bekol  from 60 of species of compiler savannah of this area. (3).  Factors influencing reduction of quality of  savannah in Bekol is : Invasion A. nilotia, bush groaning savannah, existence of tread  by animal, fire effect, and over grazing.